Endemic melioidosis in central Taiwan—A longitudinal case cohort study - Ling, Ting Ting; Lee, Su-Yin; Tsao, Shih-Ming; Liang, Keng-Wei; Wang, Wei-Yao (Frontiers in Medicine, 2023)
Background Melioidosis is a systemic and suppurative disease endemic in the Southeast Asia. In Taiwan, most cases are reported in the southern region and no relevant profiles have been reported in central region. In this study, we performed the epidemiologic and clinical analyses from the melioidosis cases in central Taiwan. Methods The demographic, clinical, laboratory, radiologic, and outcome profiles were collected retrospectively and analyzed from patients whom Burkhoderia pseudomallei was isolated from clinical specimens during the 12-year study period (2011–2022). Results Totally 11 melioidosis cases (10 males and 1 female) were diagnosed, among them only 2 (18.2%) cases lived in suburban areas. Seven (63.6%) cases were diagnosed during 2019–2020, and diabetes mellitus was the most relevant comorbidity (5, 45.4%). All cases presented with fever at arrival, but only 4 (36.4%) and 2 (18.2%) cases presented with dyspnea and shock, respectively. Pneumonitis and extrapulmonary involvement were found in 5 cases (45.4%) each. Appropriate empiric and targeted antibiotic treatments were found in 4 (36.4%) and 10 (91.0%) case, respectively. Two cases (18.2%) succumbed to infection despite appropriate treatment including targeted antibiotics. Conclusion Melioidosis has become endemic in central Taiwan. Septic patients who present with suppurative or undetermined foci and have unsatisfied responses to standard treatment should arouse clinicians to take melioidosis into consideration.